Redesigning Clinical Pathway of Elective Caesarean Section Using Activity-Based-Costing Reduce Exposure to Covid-19 - Lidia Asjanti; Nikma Fitriasari; Ali Djamhuri (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
This research objective is to discover non-value-added activities in the elective cesarean section (CS) clinical pathway (CP) through cost analysis using the ABC method and redesign elective CS CP at W Hospital. Activity-Based-Costing (ABC) is an accounting system designed through activity management. The ABC system identifies all functions in the service process chain, calculates the activity costs, and assigns costs to cost objects, such as activity-based service products. This calculation method emphasizes the service process. The ABC method is seen as a unit cost calculation system that is suitable for hospitals. CP costing using the ABC method is a cost analysis using CP as the basis for service activities. The CP of Elective CS consists of various activities. This study used a case study approach. The eight informants were the head of finance, the head of medical services and support, one ob-gyn specialist, one anesthetist specialist, one outpatient installation nurse, one midwife, one inpatient installation midwife, and onenutritionist. COVID-19 changed the procedures and influenced the activities of CS CP. The analyses were conducted using the ABC method and data triangulation. Non-value-added activities found were clinical assessment in the emergency room (ER), laboratory activities, and organic waste treatment. Non-value-added found in clinical assessment in the ER, laboratoryexaminations, and organic waste treatment. CP CS redesign consists of activities of admission, pre-operation, and post-operation, surgery, pharmacy, nutrition, medical records, laundry, billing, logistics, and management administration. The researchers suggest that W Hospital should redesign elective CS CP activities to eliminate non-value-added activities.